ANALISIS PENGELOLAAN EKSPOSUR TRANSLASI PADA PERUSAHAAN MULTINASIONAL (YAMAHA MOTOR COMPANY) - Pratiwi Badu; Sri Ratnisari Djou; Ratni Rahman (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
This study aims to analyze the management of translation exposures in a company and the impact of translation exposures for companies. Based on these objectives, researchers used a qualitative descriptive type of research. The source of the data in this study is secondary data derived from a variety of literature, documents and other written materials directly related to this research as well as information from various media. The method of data collection used in this study is documentation in which is a method of data collection by searching for things or variables with the form of defects, books, newspapers, media and so on.  The collected data is then processed with interpretive qualitative analysis. Data processing, taking place in conjunction with the data collection process, through 3 stages of data reduction, data presentation, and data verification. The results of this study can be concluded that to manage the exposure translation of the company has three methods, namely: adjusting fund flows, forward contracts and exposure netting. Impact of translation exposure for multinational companies (Yamaha motor company). Translation effect : If the company uses profit or loss due to translation in evaluating the performance of the manager of the subsidiary, then there will be several problems: